2013
DOI: 10.1371/journal.pone.0065559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior Segment Optical Tomography Parameters Measured Using a Semi-Automatic Software to Standard Clinical Instruments

Abstract: ObjectiveTo compare anterior segment parameters measured using a semi-automatic software (Zhongshan Angle Assessment Program, ZAP) applied to anterior segment optical coherence tomography (AS-OCT) images, with commonly used instruments.MethodsCross-sectional study of a total of 1069 subjects (1069 eyes) from three population-based studies of adults aged 40–80 years. All subjects underwent AS-OCT imaging and ZAP software was applied to determine anterior chamber depth (ACD), central corneal thickness (CCT), ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…For example, the mean ATA values in MPS I (12.55 mm) and MPS II (12.53 mm) were very similar to the mean anterior chamber width found by Goldsmith et al, 5 whereas in MPS VI the value was significantly smaller (11.34 mm). Similarly, previously published values for mean ACD [5][6][7] are much greater than those in our MPS VI patients, but only slightly greater than in MPS I and II. The mean CLR found by Goldsmith et al 5 was roughly equivalent to the mean values in MPS I and II (449 and 380 mm, respectively), but much lower than in MPS VI (737 mm).…”
Section: Anterior Chamber and Angle Morphologysupporting
confidence: 88%
See 1 more Smart Citation
“…For example, the mean ATA values in MPS I (12.55 mm) and MPS II (12.53 mm) were very similar to the mean anterior chamber width found by Goldsmith et al, 5 whereas in MPS VI the value was significantly smaller (11.34 mm). Similarly, previously published values for mean ACD [5][6][7] are much greater than those in our MPS VI patients, but only slightly greater than in MPS I and II. The mean CLR found by Goldsmith et al 5 was roughly equivalent to the mean values in MPS I and II (449 and 380 mm, respectively), but much lower than in MPS VI (737 mm).…”
Section: Anterior Chamber and Angle Morphologysupporting
confidence: 88%
“…6 A further AS-OCT study of 1069 normal eyes in Singaporean adults (mean age 56.9 ± 9.5 years) found mean ACD to be 3.29 ± 0.35 mm. 7 A Canadian study of 40 normal, adult eyes found the mean nasal angle to be 39.32±3.071. 8 Work conducted in Turkey on 40 normal eyes, using Visante OCT, found the mean nasal and temporal angles to be 31.2±8.71 and 32.1±8.51, respectively.…”
Section: Anterior Chamber and Angle Morphologymentioning
confidence: 99%
“…The ‘en face’ mode produces C-scans that are orientated to the frontal plane and gives transverse slices of a corneal lesion and neovascularisation—which is more intuitive to untrained operators, as opposed to the traditional cross-sectional OCT ‘B-scans’ that resemble histology slides, and are more useful for studying anterior segment anatomy 26 27. The coronal reconstruction allows for an instant overview of the corneal pathology and changes to the length, calibre and area of corneal neovascularisation, which was previously not possible with B-scan OCT views 28.…”
Section: Discussionmentioning
confidence: 99%
“…1 It also has been established as a useful tool in providing rapid, noncontact evaluation of the cornea and anterior segment. 2,3 Further technological developments also have increased the imaging capabilities of OCT in terms of speed, image resolution, and, more recently, evaluation of vascular flow. 4 These new OCT imaging techniques have been described for noninvasive evaluation of vessels within the retina and optic disc.…”
mentioning
confidence: 99%